Self-efficacy and antenatal depression mediate the relationship between third-trimester maternal health literacy and adverse pregnancy outcomes - Ling Zhang; Fengju Li; Ting Luo; Hong Yang; Guangxu Deng; Honghui Rong; Chuanfen Zheng; Lu Lu; Enyu Lei; Li Ren; Ji-an Chen (Scientific Reports, 2026)
Abstract This study aims to investigate the mechanisms through which maternal health literacy (MHL) influences adverse pregnancy outcomes (APOs), and to examine the mediating roles of self-efficacy (SE) and pre-pregnancy depression (AD) within this relationship for the first time. This cross-sectional survey recruited 322 pregnant women in the third trimester using a two-stage sampling method. Standardized instruments were used to collect data, including the Edinburgh Postnatal Depression Scale (EPDS), the MHL questionnaire, the General Self-Efficacy Scale (GSES), as well as self-reported information on demographic characteristics and indicators of APOs. Structural equation modeling (SEM) was applied to analyze the relationships and mediating pathways among the variables. Statistical significance was set at a P-value of 0.05. The incidence of APOs was 57.45%, while only 4.04% of the participants met the criteria for MHL. SEM revealed that MHL exerted a direct effect on APOs (β = -0.122, p < 0.01) and also indirectly influenced APOs through the mediating roles of SE and AD, with an indirect effect of -0.070, jointly explaining 36.46% of the association between MHL and APOs. Additionally, SE had a direct effect on APOs (β = -0.147, p < 0.01) and indirectly influenced APOs through AD, with an indirect effect of -0.046, accounting for 17.90% of the total effect. In contrast, AD had only a direct effect on APOs (β = 0.181, p < 0.01). MHL has the potential to mitigate the risk of APOs by enhancing SE and alleviating AD. These findings substantiate the theoretical pathway of “health literacy - psychological factors - pregnancy outcomes”. A multi-dimensional intervention system combining MHL promotion, SE training, and AD screening is recommended for more targeted and effective APO prevention and management.